Environmental Legislation in Indonesia - Hardjasoemantri, Koesnadi (Gadjah Mada University Press, 1989)
During the Dutch East-Indies period, environmental legislation could be characterized as "classical", In that it concerned primarily with sectoral aspects. It mainly emphasized environmental control. A few of the regulations of this period are still validon the basis of the provisions as contained In Article II concerning Transitional Provisions of the 1945 Constitution. The environmental legislation in Indonesia today therefore comprises both the laws and regulations of the preindependence period and those developed during the independence period. The 1972 Stockholm Declaration on the Human Environment gave an impetus to the development of modern environmental legislation. An important breakthrough in the overall management of the environment is the promulgation on March Tlth, 1982 of the Act No.4 of 1982 concerning Basic Provisions for the Management of the Living Environment. It encompasses all aspects of the living environment in order to form the basis for further regulations. In addition, it serves as the basis for the evaluation and adjustment of all legislations heretofore valid. The Act strongly advocates a development, which is based upon environmental consideration as a means of achieving continuity and the well-being of present and future generations. This paper studies the various implications of the principles contained in the Act.